A Solvothermal Process to Synthesize Calcium Metastannate Nanoparticles Assisted by Microwave Irradiation - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
Calcium metastannates (CaSnO3) nanoparticles were synthesized successfully using a facile microwave solvothermal route followed by further heat-treatment. Well-crystallized CaSnO3 nanoparticles were formed after heat-treatment at 800 ºC for 3 h showing a fine and homogeneous morphology with particle sizes of 20-40 nm. The synthesized CaSnO3 nanoparticles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy and transmission electron microscopy.